2023
DOI: 10.1039/d2ja00402j
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of high resolution multielemental quantitative bioimaging of animal tissue using LA-ICP-TOFMS

Abstract: Methodology for quantitative bioimaging of essential metals including Mg, Mn, Fe, Cu and Zn in tissue cryosections based on the use of high-resolution laser ablation coupled with inductively coupled plasma...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Between 10 and 15 ng Cr resulted in 3 53 Cr of ± 0.05 (2S). It was noted that samples measured by this total evaporation technique were found to have systematically lower 3 53 Cr and 3 54 Cr than were measured by the normal (non-total evaporation) TIMS method. It was suggested that this difference was caused by fractionation differences between the Cr metal and oxide species present during ionisation.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Between 10 and 15 ng Cr resulted in 3 53 Cr of ± 0.05 (2S). It was noted that samples measured by this total evaporation technique were found to have systematically lower 3 53 Cr and 3 54 Cr than were measured by the normal (non-total evaporation) TIMS method. It was suggested that this difference was caused by fractionation differences between the Cr metal and oxide species present during ionisation.…”
Section: Stable Isotope Ratio Studiesmentioning
confidence: 82%
“…Methodology for the quantitative bioimaging of essential metals including Mg, Mn, Fe, Cu and Zn in tissue cryosections based on the use of high-resolution LA-ICP-TOFMS was developed by Strekopytov et al 54 Cryosectioned gelatin standards spiked with the elements of interest were used for calibration. Analysis under 'no gas' conditions showed satisfactory selectivity and 3-fold improvement in LODs for Mn, Fe and Cu when compared with those obtained using 2.4 mL min −1 H 2 in the collision/reaction cell of the ICP-TOFMS instrument.…”
Section: Laser Ablationmentioning
confidence: 99%
“…The application of LA-ICP-TOF-MS for bioimaging has continued to demonstrate its ability as a powerful multi-elemental quasi-simultaneous technique. Strekopytov and co-workers 173 published a comprehensive study on the quantitative imaging of Cu Fe, Mg, Mn and Zn in animal tissue. A low-dispersion ablation cell was utilised alongside a dual concentric nebuliser for maximum sample transfer.…”
Section: Applications: Clinical and Biological Materialsmentioning
confidence: 99%
“…Gelatin calibration standards (10% w/w) were prepared as previously described. 33 Gelatin solutions were spiked with Eu and Ho solutions to achieve final calibration standard concentrations between 0 and 1000 mg kg −1 . A 200 μL aliquot of the spiked gelatin solutions was frozen directly inside a Leica CM1850 cryomicrotome (Leica Biosystems, Milton Keynes UK) at −17 °C, forming a rapidly freezing gelatin sphere from which 10 μm thick sections were cut onto SuperFrost microscope slides (Fisher Scientific, USA).…”
Section: Gelatin Calibration Standardsmentioning
confidence: 99%